2018
DOI: 10.3390/universe4010021
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Dark Energy Models from Galaxy Clusters and Gravitational Lensing Data

Abstract: Abstract:The Sunyaev-Zel'dovich (SZ) effect is a global distortion of the Cosmic Microwave Background (CMB) spectrum as a result of its interaction with a hot electron plasma in the intracluster medium of large structures gravitationally viralized such as galaxy clusters (GC). Furthermore, this hot gas of electrons emits X-rays due to its fall in the gravitational potential well of the GC. The analysis of SZ and X-ray data provides a method for calculating distances to GC at high redshifts. On the other hand, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 75 publications
(95 reference statements)
1
13
0
Order By: Relevance
“…Slowing down of the cosmic acceleration has been an issue of interest in several works [87][88][89][90][91][92]. In [87] this phenomenon was studied also utilising the Om(z) diagnostic, which suggests that an increase in Om(z) at lower redshift can indicate a slowing of acceleration.…”
Section: Reconstruction Of Diagnosticsmentioning
confidence: 99%
“…Slowing down of the cosmic acceleration has been an issue of interest in several works [87][88][89][90][91][92]. In [87] this phenomenon was studied also utilising the Om(z) diagnostic, which suggests that an increase in Om(z) at lower redshift can indicate a slowing of acceleration.…”
Section: Reconstruction Of Diagnosticsmentioning
confidence: 99%
“…The value of the depletion component of the bias factor related to the gas dynamical simulation from fgas (gas mass fraction) data has been obtained b f gas = 0.824 +0.033 −0.033 [110]. This value has been used in some works as a fixed value [108,111,112]. We found that fixing this parameter strongly affects the values of other parameters and the value of χ 2 as well.…”
Section: Parametersmentioning
confidence: 89%
“…Hence, observational constraints on w are crucial to unveil possible hints on the true nature of this exotic content. In this fashion, the cosmological data currently available constrain w to a very narrow band around −1 [37,38], see also [39][40][41][42][43][44][45]. Accordingly, the possibility of the expansion of the universe being fueled by phantom-type DE (w < −1) is not observationally excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the BR model here considered is just a subcase of the more general wCDM scenario, which has been thoroughly analyzed in the literature (see, for example, references [37][38][39][40][41][42][43][44][45], among others). More importantly, these specific phantom DE models have been shown to be compatible with the current observational data; see, for instance, references [37][38][39]51,56,57,79].…”
mentioning
confidence: 99%